A novel extraoral registration method for a dynamic navigation system guiding zygomatic implant placement in patients with maxillectomy defects. Issue 1 (January 2021) - Zhou, W.; Fan, S.; Wang, F.; Huang, W.; Jamjoom, F.Z.; Wu, Y.
Abstract: Zygomatic implants (ZIs) are used for the oral rehabilitation of patients with maxillectomy defects as an alternative to extensive bone grafting surgeries. New technologies such as computer-assisted navigation systems can improve the accuracy and safety of ZI placement. The intraoral anchorage of fiducial markers necessary for navigation registration is not possible in the case of a severe maxillary defect and lack of residual bone. This technical note presents a novel extraoral registration method for a dynamic navigation system guiding ZI placement in patients with maxillectomy defects. Titanium microscrews were inserted in the mastoid process, supraorbital ridge, and posterior zygomatic arch as registration markers. The mean fiducial registration error (FRE) was 0.53 ± 0.20 and the deviations between the planned and placed ZIs were 1.56 ± 0.54 mm (entry point), 1.87 ± 0.63 mm (exit point), and 2.52 ± 0.84° (angulation). The study results indicate that the placement of fiducial markers at extraoral sites can be used as a registration technique to overcome anatomical limitations in patients after maxillectomy, with a clinically acceptable registration accuracy.